Physiological and biochemical indicators of Physalis angulata L. plants submitted under salinity - Leite da Silva, Alismário; Marilza Neves do Nascimento Ribeiro,; Viviane de Jesus Carneiro,; Francisco dos Santos Neto ,; Romeu da Silva Leite,; Tamara Torres Tanan, (Comunicata Scientiae, 2021)
Saline environments may limit the growth and yield of agricultural crops, mainly in arid and semiarid regions, causing negative impacts to the plant physiology. Therefore, the objective of this work was to evaluate the growth and physiological and biochemical indicators of Physalis angulata L. plants grown in hydroponic nutrient solutions with different salinities. The experiment was conducted in a greenhouse in a floating hydroponic system, using a completely randomized design. The treatments consisted of five levels of electrical conductivity (EC) of the nutrient solution (EC0 = 0.00 – Control; EC1 = 1.80; EC2 = 3.60; EC3 = 5.40; and EC4 = 7.2 dS m-1). Plant gas exchanges, water relations, total chlorophyll contents, organic solute accumulation, and growth parameter were evaluated at 35 days after the application of the treatments. The salinity of the nutrient solution had significant effect on the variables analyzed, denoting adaptation of the plants up to the EC of 2.10 dS m-1. Decreases in photosynthetic rates at the highest salinity levels affected the plant growth, causing pronounced decreases. The P. angulata plants showed osmotic adjustment after the induction of a severe salt stress at 35 days after sowing; they accumulated organic solutes that increased leaf turgidity, even at lower salinity levels, maintaining the plant water status.